2013
DOI: 10.1108/19355181311314761
|View full text |Cite
|
Sign up to set email alerts
|

Alliance portfolio R&D intensity and new product introduction

Abstract: Purpose -The purpose of this paper is to examine whether alliance portfolio R&D intensity contributes to biopharmaceutical firms' number of new product approvals and whether alliance portfolio R&D intensity is more positively related to the number of new product approvals for pharmaceutical firms than for biotechnology firms. Design/methodology/approach -The paper employs a random effects Poisson regression model using panel data of 821 firm year observations for 146 biopharmaceutical firms operating in the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
(118 reference statements)
0
16
0
Order By: Relevance
“…Joint ventures (JVs) also permit the partners to share the risks and costs, while giving easier access to resources such as technical expertise, technology and financing. A JV can also greater flexibility to the members and the ability to react to market conditions quicker [32,[39][40][41].…”
Section: Clustersmentioning
confidence: 99%
“…Joint ventures (JVs) also permit the partners to share the risks and costs, while giving easier access to resources such as technical expertise, technology and financing. A JV can also greater flexibility to the members and the ability to react to market conditions quicker [32,[39][40][41].…”
Section: Clustersmentioning
confidence: 99%
“…Our investigation of partner type diversity addresses two important gaps in this line of research on alliance portfolios. First, so far extant studies have investigated specific types of diversity (for instance, partner type diversity) in terms of single dimensions or measures (Caner and Tyler, 2013;Jiang et al, 2010;Van de Vrande, 2013). We argue that it is imperative to adopt a multidimensional perspective of partner type diversity.…”
Section: Introductionmentioning
confidence: 98%
“…These results suggest the benefits of network "closure" (wherein a firm's partners are also partners) and access to diverse information can coexist in an alliance network and that these combined benefits increase exploratory innovation. Caner and Tyler (2013) in their study investigated the contribution of alliance portfolio R&D intensity to the firm's number of new products introduced; the study found that the R&D intensity of alliance portfolio related to the firm products innovations and introductions, also the study found that the R&D intensity of alliance portfolio has a more positive impact on the pharmaceutical companies new products innovation and introduction than those of biotechnology companies. Zheng, Li and Wu (2013) investigated the correlation between network resources and innovation performance of Chinese manufacturing firms, the study found that there is a direct contribution of network resources to firm's innovation performance.…”
Section: The Relationship Between Strategic Alliances and Firm Innovamentioning
confidence: 99%